Workshop Pembuatan Feed Instagram Taruna Siaga Bencana Di Dinas Sosial Provinsi Sumatera Selatan - Rahman, Abdul; Udjulawa, Daniel; Mulyati, Mulyati (FORDICATE, 2021)
The purpose of the implementation of this workshop can provideinsight to the TAGANA South Sumatra team in the creation of content that willbe uploaded on sosial media, one of which is Instagram. The use of Instagram,the majority of which is to use videos and pictures is an interesting thing to beable to convey and even promote activities from TAGANA South Sumatera. Theapplication used is Adobe Photoshop. In this activity using discussion methods,by applying this discussion method can provide training and mentoring. So thatthe participants can be closer and feel interested so that it is easily accepted bythe participants. The final result of this workshop the participants can movetheir creativity in creating an Instagram feed so that it attracts the attention ofthe public.